2010
DOI: 10.1189/jlb.0510281
|View full text |Cite
|
Sign up to set email alerts
|

Protection against sepsis-induced lung injury by selective inhibition of protein kinase C-δ (δ-PKC)

Abstract: Inflammation and proinflammatory mediators are activators of δ-PKC. In vitro, δ-PKC regulates proinflammatory signaling in neutrophils and endothelial and epithelial cells, cells that can contribute to lung tissue damage associated with inflammation. In this study, a specific δ-PKC TAT peptide inhibitor was used to test the hypothesis that inhibition of δ-PKC would attenuate lung injury in an animal model of ARDS. Experimental ARDS was induced in rats via 2CLP, a model of polymicrobial sepsis. Following 2CLP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 66 publications
9
84
0
Order By: Relevance
“…In summary, the present study supports the existing findings regarding the protective influence conferred by the inhibition of PKC␦ on endothelial function (5, 6) and inflammatory response (7,19) in settings of endotoxin challenge. We show for the first time that chronic deletion and acute inactivation of PKC␦ attenuate LPS-mediated pulmonary endothelial barrier dysfunction and edema formation.…”
Section: L885 Pkc␦ Deficiency and Lps-induced Alisupporting
confidence: 79%
See 3 more Smart Citations
“…In summary, the present study supports the existing findings regarding the protective influence conferred by the inhibition of PKC␦ on endothelial function (5, 6) and inflammatory response (7,19) in settings of endotoxin challenge. We show for the first time that chronic deletion and acute inactivation of PKC␦ attenuate LPS-mediated pulmonary endothelial barrier dysfunction and edema formation.…”
Section: L885 Pkc␦ Deficiency and Lps-induced Alisupporting
confidence: 79%
“…In keeping with our data, it was previously shown that intravascular administration of a cell-permeant PKC␦ inhibitor, PKC␦-TAT, attenuated edema formation in the brains of hypertensive rats via maintenance of the blood-brain barrier (33). While it was shown previously that intratracheal instillation of PKC␦-TAT peptide blunted protein levels in BAL fluid, as well as cellular infiltration into the lungs of septic rats, the route of the peptide administration suggests that the PKC␦ inhibitor was most likely affecting the alveolar epithelium and infiltrating inflammatory cells primarily (19). Thus the design and results of the current study support a critical role for PKC␦ in the pulmonary endothelium and inflammatory response to LPS-induced lung edema formation.…”
Section: L885 Pkc␦ Deficiency and Lps-induced Alimentioning
confidence: 98%
See 2 more Smart Citations
“…PKC ␦ is a serine-threonine protein kinase that can be activated by calcium and diacylglycerol and plays an important role in infl ammation (16)(17)(18). It has been shown to be involved in sepsis ( 19,20 ) and seems to mediate sepsis-induced lung injury ( 19 ). PKC ␦ also mediates high glucose-induced activation of the TLR pathway and production of infl ammatory cytokines in monocytic cells ( 21 ).…”
Section: Circulating Ox-ldl Measurementmentioning
confidence: 99%